RUSSIAN ENERGY STRATEGY FOR 21 CENTURY (Годишен зборник на Филозофски факултет - Скопје, 2011)
This paper deals with post-Soviet geopolitical space and the positions of Russia in terms of the distribution of primary energy in the various markets in post-Soviet republics, Southeast Europe and China. These opportunities positioned Russia as a major player on the market for natural gas and oil. It is quite evident that the early 21st century Russia is pursuing a pragmatic policy towards the world dominated by economic diplomacy. The economic recovery of Russia and rising living standards in recent years obviously show on the surface. Such successes are mostly due to the energy sector. To quickly fill the state budget Russia imposed high prices of natural fuels, which exports in large quantities. These indicators show that Russia is slowly but surely returning to the geopolitical scene and is again equal partner of the United States.In the region of post-Soviet republics, Russia using energy as a political tool. In South-eastern Europe, Russia strives to become the dominant distributor of energy, while in China and the Far East opens new energy markets that would ensure reliable classification given their high absorption power.
Keywords: GEOPOLITICS; RUSSIA; ENERGY; ENERGY SECURITY; ENERGY DIPLOMACY